PENGARUH AKUNTABILITAS PUBLIK, PARTISIPASI MASYARAKAT, TRANSPARANSI KEBIJAKAN PUBLIK DAN PRINSIP VALUE FOR MONEY TERHADAP PENGAWASAN KEUANGAN DAERAH (APBD) - Rosalina P Mayasari (Fakultas Ekonomi Universitas Tridinanti Palembang, 2012)
This research examines the effect of public accountability, public participation, public policy transparency and value for money principles on local finance (APBD). Sample of research using purposive sampling was a member of the board of the Commission for Economic and Financial (Commission III) and a member of Budget Council of DPRD Sumatera Selatan Province. The research proved that according to simultaneous public accountability, public participation, public policy transparency and value for money principles have had effects on local finance (APBD). In partial known that only public accountability and value for money principle influenced on local finance (APBD). While, public participation and transparency of public did not affect on local finance (APBD).Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Keywords: Public Accountability, Public Participation, Public Policy Transparency, Value for Money Principles, Local Finance (APBD)